How to read Daniel - Longman, Tremper (Downers Grove, Illinois IVP, an imprint of InterVarsity Press, 2020)
"Failing to read Daniel well means missing a critical part of God's message to us. Orienting readers to a proper engagement with Daniel, Old Testament scholar and teacher Tremper Longman III examines the book's genre, structure, historical background, and major theological message before diving deeper into each of the stories and visions"--
Introduction: Invitation to the Book of Daniel -- Part One: Reading Daniel in Its Original Setting -- Stories and visions in the midst of oppression : genre, language, and structure -- Babylonian exile and Persian (and Greek) comination : the historical setting of the Book of Daniel -- Comfort in the midst of oppression : the theme of the book -- Part Two: Reading Daniel as Six Stories and Four Visions -- Forced to train in a hostile environment, part 1: Daniel 1 -- Forced to train in a hostile environment, part 2: Daniel 2 -- God humbles powerful Nebuchadnezzar : Daniel 4 - Who can interpret the writing on the wall?: Daniel 5 -- The three friends and the fiery furnace: Daniel 3 -- Daniel in the lions' den: Daniel 6 -- "One like a Son of Man": Daniel 7 -- A ram and a goat: Daniel 8 -- Seventy weeks: the exile continues: Daniel 9 -- "Yet he will come to his end": Daniel 10:1-12:4 --"Go your way till the end": Daniel 12:5-13 -- Part Three: Reading Daniel as a Twenty-First-Century Christian -- How to live in a toxic culture: Daniel 1-6 -- Finding comfort in God's ultimate fictory: Daniel 7-12.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible; Commentaries